Assessing the B40 Housing Satisfaction of Program Perumahan Rakyat in Johor Bahru - Mirhaziq, Abdul Rahman; Wilson Rangga, Anthony Jiram; Azizah, Ismail; Ahmad Tajjudin, Rozman (2020)
Malaysian government is always trying to make sure that the citizens, especially for those low-income citizens to have a comfortable and quality house. The housing satisfaction is an important indicator to give a quality house that will create a significant impact on the individual’s quality of life. Therefore, this study attempted to identify the perimeters of housing satisfaction of the Program Perumahan Rakyat (PPR) housing scheme and further examine the relationship between socio-economics characteristics and residents’ satisfaction. A cross-sectional survey design was employed for the study, and structured questionnaires were distributed to the residents of PPR Johor Bahru. One hundred six data were analysed by Frequency Analysis, Relative Important Index and Chi-Square analysis. The study revealed that the surrounding economy, namely housing price, or re